Innovation Leaders : How Senior Executives Stimulate, Steer and Sustain Innovation. - Deschamps, Jean-Philippe. (Hoboken : John Wiley & Sons, Ltd., 2009)
Innovation leaders promote and address the innovation agenda in their company. Through personal conviction or competitive necessity they are obsessed with providing superior value to customers through innovation. They know how to mobilize their staff behind concrete innovation initiatives and do not hesitate to personally coach innovation teams. For innovation to occur leadership has to be collective. To create a momentum for innovation in their company, leaders from different functions need to team up, to build innovation networks. Innovation leadership is not just an innate talent that can be.
Chapter 11: Building An Innovation Leadership Environment: The Logitech Case1chapter 12: Attracting, Developing And Keeping Innovation Leaders; Appendix A: Innovation In Leadership And Organizational Culture Models; Appendix B: Guidelines For Using The Ideo Video For 'Idea Management' Training; Appendix C: Factors Affecting The Innovation Climate Of A Company; Index.
Print version record.
John Wiley and Sons
Keywords: Business; Affaires; businesses (business enterprises); business (commercial function); Business